Diagnostic value of cardiac magnetic resonance imaging during transition care in adolescents with Turner syndrome - Więcek, Małgorzata; Olczak, Zbigniew; Machnikowska-Sokołowska, Magdalena; Błaszczyk, Ewa; Wójcik, Małgorzata; Mazur, Artur; Starzyk, Jerzy; Kusa, Jacek; Gawlik-Starzyk, Aneta (Frontiers in Pediatrics, 2025)
BackgroundTurner Syndrome (TS) is a chromosomal disorder frequently associated with congenital cardiovascular abnormalities, particularly bicuspid aortic valve (BAV), coarctation of the aorta (CoA), and aortic dilatation. These conditions substantially increase the risk of aortic dissection. Although echocardiography (ECHO) is commonly used for cardiac monitoring, its limitations in evaluating aortic morphology require cardiac magnetic resonance imaging (CMR), as recommended by recent guidelines. CMR offers a comprehensive alternative, especially during the transition from pediatric to adult care. This timing allows for optimal cardiovascular risk assessment before conception or assisted reproductive procedures.ObjectiveTo confirm the diagnostic utility of CMR in identifying congenital and acquired cardiovascular abnormalities in adolescents with TS, and to assess the prevalence of previously undiagnosed cardiovascular defects prior to transition to adult healthcare.MethodsIn this prospective study conducted between 2020 and 2025, 43 girls with TS (mean age 16.1 ± 1.4 years) were recruited from specialized centers in southeastern Poland. Participants underwent clinical assessment and CMR in one university center using a standardized-unified protocol. Measurements included aortic diameter, aortic height index (AHI), aortic size index (ASI), and Z-scores specific to TS and the general population.ResultsCMR identified BAV in 15 (34.9%) patients, of which 60% had not been previously diagnosed by ECHO. Other abnormalities included CoA (2.3%), great vessel anomalies (9.3%), and partial anomalous pulmonary venous return (7.0%). Aortic dilatation was found in 5 patients (11.6%), all of whom had BAV. Significant differences were observed in ascending aorta diameter, AHI, and TS-specific Z-scores between patients with and without BAV (p < 0.05). No significant correlation was found between congenital heart defects and karyotype.ConclusionCMR provides critical diagnostic insight into cardiovascular defects in adolescents with TS. A substantial number of cardiovascular abnormalities, including BAV, remain undetected by ECHO alone. Integration of CMR into transition protocols may enhance early diagnosis, risk stratification, and long-term outcomes for patients with TS. Due to the increased risk of aortic dissection during pregnancy in patients with TS, CMR should be considered as a part of the evaluation before invasive fertility preservation procedures which could be offered even earlier than transitioning.